The Meaning of “Deniers of Religion” in QS. Al-Mā‘ūn [107]: 1–3: An Islamic Thought Analysis of Structural Poverty - Sarmilah Amir; Achmad Abubakar; Rahmi Damis; Syakia Syakia (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
The purpose of this study is to reveal the meaning of